Tanfīż Barāmij Al-lugat Al-ʿArabiat li Taḥsīn Mahārah Kalām Ladayya At- Ṭullāb fi Maʿhad: Implementation of Arabic Program to Improve Speaking Skill of Students in Islamic Boarding School - Mursyidatul Mahsunah; M. Akmal Binashril Hadi; Dyah Ayu Khoirunnisa; Nuril Mufidah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
Mastering a foreign language is very much needed in this modern era, so language programs can be used as an intermediary for students to master languages, especially in speaking skills, which are carried out in Islamic boarding schools. This research aims to analyze the management of the implementation of the Arabic language program to be able to form a language socio-environment for Islamic boarding school students. This research method is qualitative. The research was conducted at the Arabic Program for adults in an Islamic boarding school in Malang, Indonesia. The data collection method was carried out using observation instruments in-depth interviews and documentation. These two instruments were used to obtain data regarding the stages in implementing the Arabic language program in an Islamic boarding school Socio- environment. The data analysis technique is carried out in the stages of collecting data, reducing data, presenting data, and making conclusions. The results of the research show that there are three programs to form a language environment, including Mufrodat Yaumiyah (memorize Arabic vocabulary) which is held once a week, with the Mufrodat Yaumiyah program being able to help expand the student's vocabulary in Arabic, which can improve understanding and language skills. Then the language day program is carried out for three days starting in the morning until the afternoon. The last program is the muhadharah (show attractions of students' language skills) program which is carried out once every three weeks. The muhadharah program is carried out to measure students regarding their development and ability to use Arabic in various contexts and functions, such as a master of ceremony using Arabic, khitobah (speech or lecture), and taqdimul qissoh (storytelling). The conclusion obtained is that Islamic boarding schools must create a language environment by consistently implementing the language program. Keywords: Arabic, Language Environment, Program Management, Socio- Environment, Speaking Skills. ملخص إن إتقان لغة أجنبية أمر مطلوب للغاية في هذا العصر الحديث، لذلك يمكن استخدام برامج اللغة كوسيط للطلاب في إتقان اللغات، وخاصة في مهارات التحدث، والتي تتم في المدارس الداخلية الإسلامية. يهدف هذا البحث إلى تحليل إدارة تنفيذ برنامج اللغة العربية للتمكن من تكوين بيئة لغوية لطلاب في المعهد. طريقة البحث هذه نوعية. تم إجراء البحث في المعهد دار النون مالانج. تم استخدام طريقة جمع البيانات باستخدام أدوات الملاحظة والمقابلات المتعمقة. وقد تم استخدام هاتين الأداتين للحصول على بيانات تتعلق بمراحل تنفيذ برنامج اللغة العربية في المعهد دار النون مالانج. يتم تنفيذ تقنية تحليل البيانات في مراحل جمع البيانات وتقليل البيانات وعرض البيانات واستخلاص النتائج. تظهر نتائج البحث أن هناك ثلاثة برامج في المعهد دار النون مالانج لتكوين بيئة لغوية، منها مفردات يومية التي تقام مرة واحدة في الأسبوع، مع قدرة برنامج مفردات يومية على المساعدة في توسيع مفردات الطلاب في اللغة. اللغة العربية، والتي يمكن أن تحسن الفهم والمهارات اللغوية. ثم يتم تنفيذ برنامج يوم اللغة لمدة ثلاثة أيام تبدأ من الصباح وحتى بعد الظهر. البرنامج الأخير هو برنامج المحاضرة الذي يتم تنفيذه مرة كل ثلاثة أسابيع، ويتم تنفيذ برنامج المحاضرة لقياس الطلاب من حيث تطورهم وقدرتهم على استخدام اللغة العربية في سياقات ووظائف مختلفة، مثل استخدام اللغة العربية عند سيد الحفل، والخطابة، وتقديم القصة. الاستنتاج الذي تم التوصل إليه هو أن المدارس الداخلية الإسلامية يجب أن تخلق بيئة لغوية من خلال التنفيذ المستمر لبرنامج اللغة. الكلمات الرئيسية: إدارة برنامج، اللغة العربية، بيئة اللغوية، مهارة الكلام، الاجتماعية والبيئية